Bio-chemical amelioration effects on physico-chemical dynamics of sodic soils under rice (Oryza sativa) –wheat (Triticum aestivum) cropping system - SINGH, RANBIR; YADUVANSHI, N P S; SINGH, K N; KUMAR, SUSHIL; MISHRA, V K; SINGH, Y P; SHARMA, D K (The Indian Journal of Agricultural Sciences, 2014)
The effect of dhaincha (Sesbania aculeata) as first crop on physico-chemical dynamics and productivity of “B” class sodic soils was assessed on farmer’s field under rice-wheat cropping system to generate the knowledge of sodic soil management for increasing the soil and crop productivity for sustainable crop production in sodic soil environment. The experiment was laid out in randomized block design at ten sites having six treatment combinations of different doses of gypsum and green manuring with sesbania under two cropping sequences, i e sesbania-rice (Oryza sativa L.) -wheat (Triticum aestivum L.) and rice-wheat. Cultivation of sesbania with gypsum significantly decreased the surface soil pH from 9.3 to 8.6 and increased the hydraulic conductivity from 0.3 × 10-3 to 3.7 × 10-3 cm/hr and buildup of soil organic matter by increasing organic carbon content from 0.20 % to 0.22 % through growing of sesbania. Sesbania green manure also increased the available water content in the soil system, which enhanced soil moisture availability for longer period. As a result, rice crop yield increased by 16.2 % in sesbania-rice- wheat cropping system in comparison to rice–wheat cropping sequence because of synergistic effect of sesbania with gypsum. Consequently, residual effect of sesbania green manuring alone and in combination with gypsum significantly enhanced the wheat grain yield by 42.5 % and 72.5 % and 80% in T4, T5 and T6 treatments respectively during first year in sesbania–rice-wheat cropping sequence as compared to control. In consecutive second year, rice and wheat grain yields further enhanced by 8.1 % and 2.71% respectively, under sesbania –rice -wheat than that of rice –wheat cropping sequence. Under sesbania- rice- wheat and rice-wheat-sesbania cropping sequence, rice and wheat grain yield were similar. Hence, inclusion of Sesbania aculeata as green manure either before or after rice-wheat cropping sequence is equally better to improve the soil physical dynamics and crop productivity of ‘B’ class sodic soils in Indo-Gangetic region of Uttar Pradesh.